Chromosome analysis: what and when to request. Issue 12 (21st November 2005) - Sharkey, F H; Maher, E; FitzPatrick, D R
Abstract : Chromosome abnormalities have long been recognised as an important cause of learning disability and multiple malformation syndromes; 0.8% of live born infants have numerical or structural chromosomal anomalies resulting in an abnormal phenotype. The identification of such anomalies is important, both clinically and for accurate genetic counselling. Recently, the human genome sequence has enabled higher resolution screens for chromosome anomalies using both molecular cytogenetic and array based techniques. This review suggests a simple algorithm for the targeted use of diagnostic cytogenetic tools in specific patient groups commonly seen in paediatric practice.